The Radial Gradient Effect of HVDC Extruded Cables in Manufacturing and Application - Fei LI; Lisheng ZHONG; Wenpeng LI; Jinghui GAO; Haiyang REN; Chong ZHANG (Zhongguo dianli)
Extruded cables are widely used in HVDC projects, but the gradient effect in manufacturing and application affects their DC electrical performance significantly. The 500 kV XLPE DC cable was studied in this paper. Firstly, the field strength distribution in the uniformly insulated cable was simulated. Secondly, the temperature distribution of the insulation in the process of cross-linking and degassing was calculated, and the phase structure, by-product content and DC electrical performance of the insulation of cable at different radial positions were also measured. Finally, the field strength distribution of the insulation was simulated. The results show that there is a temperature gradient of cable insulation in the process of cross-linking and degassing, and the phase structure, and DC electrical properties of the insulation are non-uniformly distributed in the radial direction. The gradient distribution of the insulation conductivity in the radial direction results in the distortion of the field strength, in which the field strength of outer layer of insulation is greater than that of inner layer, and the field strength of the outer layer of insulation is greater than that the maximum electric strength in the uniform insulation.